Risk factors for fluoroquinolone resistance in Enterococcus urinary tract infections in hospitalized patients - RATTANAUMPAWAN, P.; TOLOMEO, P.; BILKER, W. B.; FISHMAN, N. O.; LAUTENBACH, E. (Epidemiology and infection, 2011)
Past studies exploring risk factors for fluoroquinolone (FQ) resistance in urinary tract infections (UTIs) focused only on UTIs caused by Gram-negative pathogens. The epidemiology of FQ resistance in enterococcal UTIs has not been studied. We conducted a case-control study at two medical centres within the University of Pennsylvania Health System in order to identify risk factors for FQ resistance in enterococcal UTIs. Subjects with positive urine cultures for enterococci and meeting CDC criteria for healthcare-acquired UTI were eligible. Cases were subjects with FQ-resistant enterococcal UTI. Controls were subjects with FQ-susceptible enterococcal UTI and were frequency matched to cases by month of isolation. A total of 136 cases and 139 controls were included from 1 January 2003 to 31 March 2005. Independent risk factors [adjusted OR (95% CI)] for FQ resistance included cardiovascular diseases [2·24 (1·05–4·79), P=0·037], hospitalization within the past 2 weeks [2·08 (1·05–4·11), P=0·035], hospitalization on a medicine service [2·15 (1·08–4·30), P<0·030], recent exposure to β-lactamase inhibitors (BLIs) [14·98 (2·92–76·99), P<0·001], extended spectrum cephalosporins [9·82 (3·37–28·60), P<0·001], FQs [5·36 (2·20–13·05), P<0·001] and clindamycin [13·90 (1·21–10·49), P=0·035]. Use of BLIs, extended spectrum cephalosporins, FQs and clindamycin was associated with FQ resistance in enterococcal uropathogens. Efforts to curb FQ resistance should focus on optimizing use of these agents.